The Influence of Community Education Level on Entrepreneurial Spirit - K. Adam, Vira Deyanti; Hafid, Radia; Sudirman, Sudirman (JUPE : Jurnal Pendidikan Mandala, 2023)
This research aims to determine whether education level influences entrepreneurial spirit in uekambuno village, Ulubongka subdistrict, Tojo Una-UnaRegrency, Central Sulawesi Province. This research employs a quantitative approach with an explanatory research method. The data used are primary data obtained through the distribution of questionnaires to the community in Uekambuno Village, Ulunongka Subdistrict, Tojo Una-Una Regency, and Central Sulawesi Province. A sample of 30 respondents was drawn. The data analysis technique involutes simple linear regression. The results indicate an influence of educational level on entrepreneurial spirit in Uekambuno village, Ulubongka sub-district, Tojo Una-Una regency, Central Sulawesi Province. The education level influences the entrepreneurial spirit by 23.9%, while unexamined variables influence the remaining 76.1%.